2021
DOI: 10.1101/2021.12.13.472426
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Absolute Scaling of Single-Cell Transcriptomes Reveals Pervasive Hypertranscription in Adult Stem and Progenitor Cells

Abstract: Hypertranscription facilitates biosynthetically demanding cellular state transitions through global upregulation of the nascent transcriptome. Despite its potential widespread relevance, documented examples of hypertranscription remain few and limited predominantly to early development. This limitation is in large part due to the fact that modern sequencing approaches, including single-cell RNA sequencing (scRNA-seq), generally assume similar levels of transcriptional output per cell. Here, we use molecule cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…Murine hematopoietic stem cells need to tightly control their PT to maintain their function 9 . It has also been shown that hematopoietic, epidermal, and colonic epithelium progenitor cells are characterized by a hypertranscriptional state relative to the stem cells they descend from 10 . Recently, species‐specific degradation kinetics and delayed synthesis of HES7, the core gene of the segmentation clock, have been linked to differences in segmentation clock frequency between murine and human organisms, suggesting that PT may define the velocity of development and cell differentiation 11,12 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Murine hematopoietic stem cells need to tightly control their PT to maintain their function 9 . It has also been shown that hematopoietic, epidermal, and colonic epithelium progenitor cells are characterized by a hypertranscriptional state relative to the stem cells they descend from 10 . Recently, species‐specific degradation kinetics and delayed synthesis of HES7, the core gene of the segmentation clock, have been linked to differences in segmentation clock frequency between murine and human organisms, suggesting that PT may define the velocity of development and cell differentiation 11,12 .…”
Section: Introductionmentioning
confidence: 99%
“…9 It has also been shown that hematopoietic, epidermal, and colonic epithelium progenitor cells are characterized by a hypertranscriptional state relative to the stem cells they descend from. 10 Recently, species-specific degradation kinetics and delayed synthesis of HES7, the core gene of the segmentation clock, have been linked to differences in segmentation clock frequency between murine and human organisms, suggesting that PT may define the velocity of development and cell differentiation. 11,12 Finally, alterations in protein turnover have been linked to leukemia 9 or neurodegenerative diseases such as Alzheimer's and Parkinson's diseases, due to the accumulation of aggregationprone proteins.…”
Section: Introductionmentioning
confidence: 99%